The role of competition as a mediator between financial liberalization and financial stability / Nur Afizah Muhamad Arifin …[et al.] - Muhamad Arifin, Nur Afizah; Mohd Arifin, Noraini; Ramly, Zulkufly; Hashim, Maryam Jameelah (Universiti Teknologi MARA Cawangan Selangor, 2019)
The shift from financial repression to financial liberalization causes cross-border capital flows and brought dramatic changes to the financial sector. In this regard, the financial sectors, acts as financial intermediary which plays a significant role in mobilizing funds between surplus and deficit units. Furthermore, financial liberalization creates higher competition and could have negative impact towards financial stability due to excessive risk taking. This study’s research model focuses on examining the impact of competition on the relationship between financial liberalization and financial stability. This model was analyzed by using the PLS-SEM and it was found that the measurement model explains 19% of the substantial amount of variance in financial stability. Based on this finding, this study will theoretically contribute in extending the competition stability view and competition fragility view as determiners of financial stability. Based on the empirical results, it can be concluded that in the presence of competition, financial liberalization has a significant effect on financial stability